A comprehensive update on the pharmacological management of heterotopic ossification following hip arthroplasty: a level I evidenced based expert opinion. (3rd July 2022) - Migliorini, Filippo; Asparago, Giovanni; Oliva, Francesco; Cuozzo, Francesco; Maffulli, Nicola
ABSTRACT: Introduction: Heterotopic ossification (HO) of the hip joint may happen accompanying skeletal muscle trauma or surgical procedures. The pharmacological prophylaxis of heterotopic ossification (HO) following total hip arthroplasty (THA) is debated. Areas covered: This expert opinion aims to systematically investigate the efficacy of current pharmacological options as prophylaxis for HO following THA. Expert opinion: The current evidence identified celecoxib, naproxen, and diclofenac as best option for the prevention of HO in patients who undergo primary THA. The most appropriate pharmacotherapy for the prevention of HO is still debated and should be customized according to patients' comorbidities and medical history. For patients with cardiovascular comorbidities, naproxen, or diclofenac should be considered along with proton pump inhibitors to prevent gastrointestinal complications. For patients with history of gastrointestinal disease, celecoxib can be recommended. These conclusions must be considered within the limitations of the present investigation. Between studies, heterogeneities in the administration protocols were evident. In some RCTs, the length of the follow-up was shorter than 12 months. The current clinical practice would benefit of high-quality recommendations and the development of the shared official guidelines.